(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
the article examines the socio-psychological competence of leaders necessary for the implementation of effective management activities. Some individual qualities of the personality of managers are studied, which are characterized by a high level of development of management and socio-psychological competence, as well as possible methods and forms of measurement, analysis and assessment of professionally important qualities of an individual. This means that the study of the personality of the leader and aspects of managerial activity should be carried out on the basis of an integrated approach to the effective professional development of the personality of the leader and the formation of a worthy attitude towards his professional activity. At the same time, complex assessment includes an assessment of the activity as a whole, the entire volume of its functions and the personality of the leader. The purpose of the article is to determine the degree of importance of the professional and psychological training of leaders for their socio-psychological competence and effectiveness in management activities, as well as for the correct Organization of training of the executive personnel Reserve.